Corak Pemikiran Modern Pendidikan Islam - M Munawir (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2016)
Mohammad Natsir proposed a concept of education by potraying a dichotomy between general seducation and religious education. He suggested the oneness of God (Tawheed) as a priciple of education. The Islamic education ideology is based on the Tawheed. He states that the ideology of education should have a definite vision, mission, and objectives so that it could produce a positive contribution to the nation. This is relevant with the condotion of educational traits ini Indonesia in which it is hoped to be able to manage the characteristic of Indonesian identity. People recognize Natsir as preacher and a political figures. However, they don’t know his role in education. He is actually a great thinker on education field. His concept actually place the Tauheed as the font liner in developing education by the idea that it will guide to the better future of Indonesians throughout the education sector. His ideas are taken as reference by many Islamic scholars and thinkers. Because of this. He is called as neo-modernist.